2018
DOI: 10.3171/2017.3.peds16596
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging in the prone position and the diagnosis of tethered spinal cord

Abstract: OBJECTIVETethered cord syndrome (TCS) is a neurosurgical disorder with varied clinical manifestations believed to result from vascular compromise due to stretch forces on the spinal cord. Conventional supine MRI findings may include a low-lying conus medullaris, thickened or fat-infiltrated filum terminale, or lipoma; however, imaging sensitivity and specificity for tethered cord can be low. The purpose of this study was to evaluate the utility of prone MRI in the dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“… 65 , 66 This is now used diagnostically, for example, to identify a tethered spinal cord using MRI in the prone position. 67 , 68 Further, the material properties of the spinal cord change with normal movement of the spine. 69 , 70 This is largely in flexion, where the spinal cord lengthens, 71 , 72 and the cross-sectional area of the spinal cord reduces, 73 , 74 estimated to exhibit a strain of 12% in normal physiological conditions.…”
Section: Introductionmentioning
confidence: 99%
“… 65 , 66 This is now used diagnostically, for example, to identify a tethered spinal cord using MRI in the prone position. 67 , 68 Further, the material properties of the spinal cord change with normal movement of the spine. 69 , 70 This is largely in flexion, where the spinal cord lengthens, 71 , 72 and the cross-sectional area of the spinal cord reduces, 73 , 74 estimated to exhibit a strain of 12% in normal physiological conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Although performing an MRI in the prone position is unusual and some technical difficulties would need to be overcome, some recent imaging studies reported the feasibility of performing MRIs in the prone position. 32,33 In the future, further research on performing MRIs in the prone position are needed to resolve this issue.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of a tight filum terminale was further evaluated by performing MRI on all patients while in prone position. A forward movement of the canal width by at least 10% was considered normal, thereby ruling out the tightness of the filum terminale [13]. The presence of cord tethering or tightness of the filum terminale was further confirmed during surgery by two skilled neurosurgeon observers for each case.…”
Section: Evaluation Of Tethered Cord Syndromementioning
confidence: 99%